The relationship between plasma hyaluronan levels and anthracycline-related cardiotoxicity in breast cancer patients. (1st September 2016) - Inanc, Mehmet Tugrul; Karadavut, Serhat; Aytekin, Metin; Duran, Ayse Ocak; Derya, Muazzez; Akpek, Mahmut; Sahin, Omer; Kalay, Nihat; Karaca, Halit; Ozkan, Metin; Inanc, Mevlude
Abstract: Aim: Anthracycline-derived antineoplastic agents are used as the main form of treatment in many malignant diseases, including breast cancer and childhood cancers. Cardiotoxicity is one of the most feared life-threatening complications of cancer therapy. In the present study, we aimed to investigate the relationship between plasma hyaluronan (HA) levels and anthracycline-induced cardiotoxicity. Materials and methods: Fifty eight of 73 female patients who were diagnosed with breast cancer and treated with a chemotherapy regimen including anthracycline were enrolled in this study. Anamneses were taken from each patient before and after chemotherapy. Further, physical examinations, electrocardiography, and transthoracic echocardiography were performed, and plasma hyaluronan levels were determined by using ELISA assay for each patient before and after treatment. Results: Following anthracycline-based chemotherapy, the average left ventricular ejection fraction decreased (62.6 ± 3.7% vs. 58.6 ± 4.4%, p < 0.001), and diastolic functions significantly deteriorated (p < 0.001). However, troponin and hyaluronan levels significantly increased following chemotherapy [Troponin (ng/ml, mean ± SD): before 0.01 ± 0.002, after 0.037 ± 0.02, p < 0.001], [Plasma HA (ng/ml, mean ± SD): before 41.3 ± 5.4, after 70 ± 8.5, p < 0.001]. The increase in troponin values correlated with systolic dysfunction (p = 0.002), but did not correlate with diastolic dysfunction (p = 0.661). Significant correlations were found between systolic/diastolic dysfunction and plasma HA levels (r = 0.417, p = 0.001; r = 0.339, p = 0.009, respectively). Conclusions: Both systolic and diastolic functions were significantly deteriorated after chemotherapy. In addition, plasma levels of HA and troponin increased after treatment. Further, both systolic and diastolic dysfunctions were found to correlate with serum HA levels. All these data suggest that HA might have a function on anthracycline-induced cardiotoxicity.